Effect of Weather Conditions on the Fatty Acid Composition of Medium-Growth Chicken Reared in Organic Production System - Sarmiento-García,A (2021)
ABSTRACT A total of 160 medium-sized one-day-old male chicks reared in organic conditions were studied individually from the first day of their life until slaughter (120 days). Two weather periods were considered, being period C colder than period H. A total of 24 chickens per period were randomly selected, then the breast muscle (m. Pectoralis major) was extracted for analysis. Individual fatty acids were measured by gas chromatography and expressed in grams per 100 g of fat. From the values obtained, total lipid fractions were calculated. Near infrared spectroscopy spectra (NIRS) were recorded on the surface of the breast without manipulating. Breast from chicken reared in H period had significantly lower (p<0.05) saturated fatty acids / polyunsaturated fatty acids (SFA / PUFA) ratio, and increased (p<0.05) content in PUFA and n-6. However, no significant differences were observed on the content of individual fatty acid. NIR system was not able to correctly classify the samples according to the breeding period.